Oral cavity evaluation and dental chart registration of coati (Nasua nasua) in captivity - Freitas, Elisangela R. [UNESP]; Rahal, Sheila Canevese [UNESP]; Teixeira, Carlos Roberto [UNESP]; Teixeira, Rodrigo H. F.; Mendes, Guilherme M.; Gioso, Marco A. (Nichepubs, 2008)
The aims of this study were to develop a dental chart evaluate any oral cavity disease, develop gypsum models the dental arches, and to register the occlusions found in coatis (Nasua nasua) in captivity. Formulation of the dental chart was assisted by intraoral radiographs from the head of an adult coati cadaver of the same species with the following dental formula: I 3/3, C 1/1, P 4/3, M 2/2. Seven live coatis of the Nasua nasua species were evaluated. Five of the seven coatis presented with various dental abnormalities as follows: dental plaque (71.4 %), gingivitis (71.4 %), periodontitis (57.1 %), dental stain (42.9 %), dental abrasion (57.1 %), dental fracture (57.1 %), pulp exposure (42.9 %), malocclusion (5 7.1 %) and supernumerary teeth (14.2 %).